Synthesis and Photoluminescence Properties of Alkylbromoporphyrin - Ari Yustisia Akbar; Tania Avianda Gusman (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2021)
The usage of porphyrin as a light-harvesting chromophore is considered as one of the keys to obtaining low-cost and high-efficiency dye-sensitized solar cell (DSSC). In this paper, a novel porphyrin, 5,10,15-tris(nitrophenyl)-20-(p-(11-bromo)dodecoxyphenyl))porphyrin, having a long alkyl chain and three nitro groups was synthesized. The nitro groups serve as anchoring groups to TiO2 surfaces and long alkyl chain prevents unwanted dye aggregation. The porphyrin was synthesized by condensation of p-(12-Bromododecoxy)benzaldehyde and pyrrole in propionic acid according to an adaptation of the general Rothemund method [1]. p-(12-Bromododecoxy)benzaldehyde was synthesized by nucleophilic substitution reaction between 4-hydroxybenzaldehyde and 1,12-dibromododecane in acetone. The reaction products were analyzed by 1H-NMR and mass spectroscopy. The absorption and fluorescence spectra of the porphyrin were also recorded. As results, the absorption spectrum of the porphyrin consists of a strong Soret and four weak Q-band. Compared to 5,10,15-tris(nitrophenyl)-20-(p-(11-bromo)dodecoxyphenyl))porphyrin spectrum, there is no wavelength shifting because of the incorporation of the alkyl chain. The fluorescence spectrum of the porphyrin shows two characteristic emission bands and the intensity ratio of those emission bands is always constant when irradiated by different excitation wavelength related to Soret and Q-band.